Etching-assisted synthesis of single atom Ni-tailored Pt nanocatalyst enclosed by high-index facets for active and stable oxygen reduction catalysis. (1st December 2022) - Sun, Lian; Wang, Qichen; Ma, Ming; Xie, Haijiao; Zhou, Xingui
Abstract: Designing structure and compositional distribution are critical for developing high-performance Pt-based oxygen reduction reaction (ORR) catalysts for fuel cells and other metal-air batteries. Here, we report a facile method to simultaneously dope single-atom Ni and expose high-index facets (HIFs) for Pt nanocrystals by chemical etching with HCl. The optimized catalyst displays a mass activity of 2.63 A mgPt −1 and specific activity of 4.15 mA cmPt −2 (0.1 M HClO4 ), which are both ∼15 times higher than those of commercial 20 wt% Pt/C. Particularly, it shows remarkably enhanced cycling stability. The density functional theory calculations and experimental results demonstrate that the construction of HIFs and single-atom Ni activation in Pt lattice lessen oxygen adsorption energy, which causes enhanced activity. Besides, regulating sub-layer Ni distribution also strengthens the Pt-Pt bonds on the surface, resulting in improved ORR stability. Graphical Abstract: A novel single atom Ni tailored Pt nanocatalyst enclosed with high-index facets (HIFs) was synthesized by chemical etching of hydrochloric acid. Both single atom Ni modification and HIF effect contribute to the decreased oxygen adsorption. Thus, it exhibits ∼15 times higher mass activity and specific activity than Pt/C in ORR, and possesses remarkably enhanced stability after 10, 000 cycles. ga1 Highlights: A single atom Ni-tailored Pt nanocatalyst enclosed with high-index facets was synthesized by chemical etching from acid. This catalyst shows a ∼15 times higher activity with a greatly enhanced stability than those of Pt/C. DFT calculations demonstrate that both single atom Ni and high index facets contribute to the improved ORR performance. The assembled H2 -O2 cell and zinc-air battery with this catalyst also show high peak power density.